2020
DOI: 10.1109/access.2020.2965081
|View full text |Cite
|
Sign up to set email alerts
|

Resource Allocation for Hybrid RF/FSO Multi-Channel Multi-Radio Wireless Mesh Networks

Abstract: The overwhelming data rates in next generation wireless networks impose a burden on the high-capacity network planning. One promising strategy to meet the demand for high-capacity communications is to augment radio frequency (RF) based multi-channel multi-radio (MCMR) wireless mesh network (WMN) by free-space optics (FSO). In this paper, we construct a hybrid RF/FSO MCMR WMN topology and address its resource allocation (RA) problem in terms of interface assignment, channel allocation, routing, FSO link allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In [240], a heuristicbased backhaul link selection scheme to minimize cost under data rate, connectivity, and reliability constraints was proposed for an Int-RF/FSO multi-band backhaul network. In [241], the authors developed an RF/FSO multi-band wireless mesh network and focused on sum rate optimization via route selection, topology control, channel allocation, and interface assignment under flow conservation, routing, FSO link allocation, logical topology, link capacity, delay, and fairness constraints. Due to the nonconvex nature of the optimization problem, the authors relied on the commercial solver Gurobi and metaheuristics to propose an iterative local search algorithm.…”
Section: Rf/fso Mbnsmentioning
confidence: 99%
“…In [240], a heuristicbased backhaul link selection scheme to minimize cost under data rate, connectivity, and reliability constraints was proposed for an Int-RF/FSO multi-band backhaul network. In [241], the authors developed an RF/FSO multi-band wireless mesh network and focused on sum rate optimization via route selection, topology control, channel allocation, and interface assignment under flow conservation, routing, FSO link allocation, logical topology, link capacity, delay, and fairness constraints. Due to the nonconvex nature of the optimization problem, the authors relied on the commercial solver Gurobi and metaheuristics to propose an iterative local search algorithm.…”
Section: Rf/fso Mbnsmentioning
confidence: 99%
“…The client coverage α(G) is given by (11). In addition, for the purpose of creating the fitness function, the connectivity factor between the routers is considered and denoted as θ(G) and given by (12). Therefore, the weighted sum method is used, which turns a multi-objective problem into a single-objective problem by adding up each goal and multiplying it by a weight set by the user.…”
Section: ) the Fitness Functionmentioning
confidence: 99%
“…The challenge of effectively deploying WMNs might, in some respects, be understood as an issue pertaining to the location of the facilities involved [11], [12], [13], [14]. Prior research conducted over a long time period outlined and confirmed the NP-hardness of this subject [13].…”
Section: Introductionmentioning
confidence: 99%
“…They obtained lower bounds on the overall network interference by considering the channel assignment problem as a semi-definite program and a linear programming formulation of their optimization problem. Y. Zhao et al focused on resource allocation in WMNs considering multi-channel and multi-radio approaches [ 21 ]. They proposed an optimization model which formulates each phase as a mixed integer linear problem.…”
Section: Related Workmentioning
confidence: 99%